Structural response of concrete gravity dams under blast loads - Sevim, Baris; Toya, Ahmet Tugrul (TECHNO-PRESS, 2020)
Concrete dams are important structures due to retaining amount of water on their reservoir. So such kind of structures have to be designed against static and dynamic loads. Especially considering on critical importance against blasting threats and environmental safety, dams have to be examined according to the blast loads. This paper aims to investigate structural response of concrete gravity dams under blast loads. For the purpose Sariyar Concrete Gravity Dam in Turkey is selected for numerical application with its 85 m of reservoir height (H), 255 m of reservoir length (3H), 72 m of bottom and 7 m of top widths. In the study, firstly 3D finite element model of the dam is constituted using ANSYS Workbench software considering dam-reservoir-foundation interaction and a hydrostatic analysis is performed without blast loads. Then, nearly 13 tons TNT explosive are considered 20 m away from downstream of the dam and this is modeled using ANSYS AUTODYN software. After that explicit analyses are performed through 40 milliseconds. Lastly peak pressures obtained from analyses are compared to empirical equations in the literature and UFC 3-340-02 standard which provide unified facilities criteria for structures to resist the effects of accidental explosions. Also analyses' results such as displacements, stresses and strains obtained from both hydrostatic and blasting analysis models are compared to each other. It is highlighted from the study that blasting analysis model has more effective than the only hydrostatic analysis model. So it is highlighted from the study that the design of dams should be included the blast loads.
Keywords: blast load; concrete gravity dam; explicit analysis; structural response; TNT explosive; Construction & Building Technology; Engineering; Materials Science